PESANTREN TRANSFORMATION IN THE DIGITAL ERA: Challenges, Adaptation, And Technological Moderation - Murdianto Murdianto (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
Pesantren, as the oldest Islamic educational institution in Indonesia, has played a crucial role in shaping the morals and character of the nation. With the rapid development of technology, pesantren are now faced with the challenge of adapting without losing their traditional values. This article discusses the transformation of pesantren in facing the digital era, including curriculum innovations that integrate science, technology, and vocational education. Through technological adaptation, pesantren now utilise digital devices and online media to increase access to information for santri and enrich teaching methods. However, this adaptation is not free from challenges, especially limited infrastructure and resources in remote areas. Moderation in the use of technology is an important approach, maintaining a balance between religious education and modern skills. Technology is also utilised as an effective means of da'wah and supports digital ethics education, forming santri who are not only religious but also competitive in the world of work. This transformation is expected to strengthen the role of pesantren as relevant and adaptive educational institutions, in line with the times but still adhering to Islamic principles.